2008
DOI: 10.1186/1744-8069-4-55
|View full text |Cite
|
Sign up to set email alerts
|

FMRI Connectivity Analysis of Acupuncture Effects on an Amygdala-Associated Brain Network

Abstract: BackgroundRecently, increasing evidence has indicated that the primary acupuncture effects are mediated by the central nervous system. However, specific brain networks underpinning these effects remain unclear.ResultsIn the present study using fMRI, we employed a within-condition interregional covariance analysis method to investigate functional connectivity of brain networks involved in acupuncture. The fMRI experiment was performed before, during and after acupuncture manipulations on healthy volunteers at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
120
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 122 publications
(126 citation statements)
references
References 54 publications
5
120
0
1
Order By: Relevance
“…More recently, Qin et al used the nonrepeated eventrelated fMRI (NRER-fMRI, Fig. 1A) design to investigate delayed responses after acupuncture administration (3,15). As compared with the ''on-off'' design paradigm, this one has the advantage of considering the spatial and temporal information respectively in the whole process of acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Qin et al used the nonrepeated eventrelated fMRI (NRER-fMRI, Fig. 1A) design to investigate delayed responses after acupuncture administration (3,15). As compared with the ''on-off'' design paradigm, this one has the advantage of considering the spatial and temporal information respectively in the whole process of acupuncture.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al [148] and Bai et al [149] found that acupuncture stimulation may induce the modulation of thè`a cupuncture-related'' network, represented by significant changes of functional connectivity in several regions of the brain, such as the bilateral frontal gyrus, bilateral temporal gyrus, inferior parietal lobe, middle occipital gyrus, pre-and postcentral gyrus, anterior cingulate cortex (ACC), parahippocampus, insula, tonsil, pyramis, culmen, precuneus and cuneus. Qin et al [150,151] identified an amygdala-related network during the resting state both after verum and penetrating sham acupuncture at a nearby point. Compared to sham, verum acupuncture increased the connectivity between the amygdala, the PAG (periaqueductal gray) and the insula, and decreased the connectivity between the amygdala with the middle frontal cortex, the postcentral gyrus and the posterior cingulate cortex (PCC).…”
Section: Descriptive Findings Of Other Comparisons and Resultsmentioning
confidence: 99%
“…Qin et al have proposed a newly experimental paradigm, namely the nonrepeated event-related fMRI (NRER-fMRI) design, to explore the prolonged effects of acupuncture on the restingstate brain networks [34]. Compared with the acupuncture at a non-acupoint (NAP), there was a higher level of correlations among the amygdala-associated networks following acupuncture at ST36.…”
Section: Sustained Effects Of Acupuncture and Its Influence On Fmri Rmentioning
confidence: 99%